Stroke and status epilepticus: stroke type, type of status epilepticus, and prognosis - (:unkn) unknown (W B SAUNDERS CO LTD, 2003)
Even though stroke is known to be a common cause of status epilepticus (SE), the types of stroke or SE that may be associated are not yet clearly defined. The aims of this study were to assess the timing and type of SE in stroke patients and to observe the effects of stroke and the type of SE on the response to treatment and mortality. From May 1998 to May 2001 a total of 121 patients were admitted with SE. Among these, 30 cases (24.8%) of poststroke SE were identified and evaluated. There were 20 early-onset, and 10 late-on et SE. All stroke types were evenly distributed within the early-onset group, whereas only ischaemic stroke was found in the late-onset group. Posterior cerebral artery (PCA) infarcts were significantly more common within the latter (P: 0.0017). Nonconvulsive SE (NCS) was more frequent than convulsive SE (CS) in the early-onset group (P: 0.0352). There. was a delay in the time-to-treatment for NCS compared to CS (P: 0.0007). Without, however any effect. on the rate of response to first step treatment (intravenous diazepam and phenytoin; P: 0.6334). Thirteen patients died (43.3%) during hospitalisation. Disability was significantly associated with higher mortality in the early-onset group (P: 0.0201). As a conclusion, NCS seems to be an important issue in stroke, thus requiring a high degree of suspicion in an acute stroke setting to avoid further neuronal injury and morbidity. (C) 2.002 BEA Trading Ltd. Published by Elsevier Science Ltd. All rights reserved.
Keywords: status epilepticus; stroke; nonconvulsive status epilepticus; EARLY SEIZURES; RISK-FACTORS; EPILEPSY; PREDICTORS; MORTALITY; FREQUENCY; ONSET